Iodine-Induced Retinopathy: A Case Report - Kobat, Sabiha Gungor; Gul, Fatih Cem; Turgut, Burak (Turkish Ophthalmological Soc, 2020)
Potassium iodide is used as an iodine supplement in salt as part of a national program in Turkey. An overdose of iodine has a toxic effect on the retinal pigment epithelium and photoreceptors. The case presented here is a patient who developed retinopathy following consumption of an excessive dose of iodine.
Keywords: Iodine; toxic; retinopathy